ICT integration into English language teaching-learning: Insights from some private higher education institutions - Haerazi, Haerazi (Englisia: Journal of Language, Education, and Humanities, 2024)
The integration of technology within language classrooms is a pivotal facet of modern education. Due to this, this study aims to investigate the English lecturers’ views about the use of educational technology in English language classrooms and the English teachers’ implementation strategies about ICT integration into ELE programs in higher education. The study employs a qualitative research approach to facilitate an in-depth exploration and elucidation of its findings. The participants under scrutiny consisted of English lecturers affiliated with English language education study programs situated within private universities located in the West Nusa Tenggara region. The selection of participants was facilitated through the utilization of a convenient sampling method, which was deemed appropriate for the purposes of data collection in this study. In total, the study encompassed the involvement of 25 participants, and it is noteworthy to mention that the composition of this participant pool exhibited certain demographic characteristics. This study used semi-structured interview guidelines as the research instruments. The data analysis process encompassed several key stages, including data condensation, data display, and drawing conclusions. The research findings highlight a diverse landscape of ICT integration among English lecturers in private universities in West Nusa Tenggara, Indonesia. While some educators demonstrate a propensity for innovative and multifaceted technology integration, others exhibit more conventional and hardware-focused approaches. It can be concluded that English lecturers have views about the technology use that should be optimized in the ICT integration within English language education programs.